PENGARUH MODAL USAHA, PENGGUNAAN INFORMASI AKUNTANSI, DAN LITERASI FINANSIAL TERHADAP KEBERHASILAN UMKM DI KOTA KUALASIMPANG - Fitri Wahyuni Wulan Dari; Dewi Rosa Indah; Nasrul Kahfi Lubis (Jurnal Mahasiswa Akuntansi Samudra, 2022)
The purpose of this study was to determine the effect of venture capital, use of accounting information, and financial literacy on business success in Micro, Small and Medium Enterprises (MSMEs) in Kualasimpang City. The research sample was taken by purposive sampling method. The number of samples used in the study were 94 respondents. Data analysis using Multiple Linear Regression Analysis with Y = 16,416 + 0.249x1 + 0.101x2 + 0.344x3. The results of the t test are known that business capital has a significant effect on business success in MSMEs in Kualasimpang City with a tsig value. 0.000 < 0.05 and the hypothesis is accepted, the use of accounting information has a significant effect on business success in MSMEs in Kualasimpang City with a tsig value. 0.032 <0.05 and the hypothesis is accepted, and financial literacy has a significant effect on business success in MSMEs in Kualasimpang City with a tsig value. 0.000 < 0.05 and the hypothesis is accepted. The results of the F test show that Business Capital, Use of Accounting Information, and Financial Literacy simultaneously have a significant effect on the success of MSMEs in Kualasimpang City with the Fsig value. 0.000 < 0.05. The results of the coefficient of determination test show that the contribution of the variables of working capital, use of accounting information, and financial literacy affect business success in MSMEs in Kualasimpang City by 51.1%, while the remaining 48.9% is influenced by other variables not examined in this study.